Optic Cup Segmentation for Glaucoma Detection Using Low-Rank Superpixel Representation - Xu, Yanwu; Duan, Lixin; Lin, Steve; Chen, Xiangyu; Wong, Damon Wing Kee; Wong, Tien Yin; Liu, Jiang (Medical Image Computing and Computer Assisted Intervention (MICCAI), 2014)
We present an unsupervised approach to segment optic cups in fundus images for glaucoma detection without using any additional training images. Our approach follows the superpixel framework and domain prior recently proposed in [1], where the superpixel classification task is formulated as a low-rank representation (LRR) problem with an efficient closed-form solution. Moreover, we also develop an adaptive strategy for automatically choosing the only parameter in LRR and obtaining the final result for each image. Evaluated on the popular ORIGA dataset, the results show that our approach achieves better performance compared with existing techniques.